A clinical review of maternal bacteremia. Issue 3 (14th December 2013) - O'Higgins, Amy C.; Egan, Aileen F.; Murphy, Olivia C.; Fitzpatrick, Christopher; Sheehan, Sharon R.; Turner, Michael J.
Abstract: Objective: To carry out a 4‐year review of cases of bacteremia among obstetric patients. Methods: In a retrospective review, all cases of maternal bacteremia between 2009 and 2012 were identified from the laboratory database of Coombe Women and Infants University Hospital, Dublin, Ireland. The clinical records of each case were assessed. Results: During the study period, 37 584 obstetric patients attended the hospital. There were 58 cases of bacteremia: 19 were diagnosed prepartum, 20 intrapartum, and 19 postpartum. There were no maternal deaths. Two cases resulted in septic shock. Four cases were associated with early pregnancy loss, and 2 with stillbirth. Fifty‐four cases occurred among 34 956 women who delivered a neonate weighing 500 g or more (0.15%). Escherichia coli most frequently caused prepartum and postpartum bacteremia, whereas Streptococcus agalactiae (β‐hemolytic, Lancefield group B) most frequently caused intrapartum bacteremia. There was no association between the development of bacteremia and maternal risk factors including employment status, obesity, parity, smoking status, and maternal age. Most organisms cultured were sensitive to first‐line antibiotics; there were no cases of bacteremia caused by multi‐drug resistant organisms. Conclusion: The incidence of maternal bacteremia in the study population was low and was usually associated with good maternal and fetal outcomes.